EFFECT OF INFLATION, EXCHANGE RATE, INTEREST RATE, TOTAL ASSET TURNOVER ON SHARE PRICES IN PROPERTY COMPANIES, REAL ESTATE, AND CONSTRUCTION BUILDING (Jurnal Ipteks Terapan, 2022)
Information of the cycles share prices up and down at a certain company they can be used as a model before making investment transaction in the stock market as a inflation, intrest rate, exchange rate, etc. Shares are bonds that evidence of a person's ownership of a company. In recent years share prices of property, real estate, and construction building had price increase and decrease. Share prices switch result of the macroeconomic is inflation, interest rate, exchange rate, and total asset turnover. This research purposeful to find out how much significant effect of inflation, exchange rate, interest rate, total asset turnover on share prices in property companies, real estate, construction building listed on the IDX 2018-2020 period. The study conducted with a data measurement of the annual financial statements obtained from IDX. Results showing inflation, interest rate, and exchange rate having a significant low value in affecting share prices. while the total asset turnover having a significant high value in share prices